LEMBAR KERJA SISWA (LKS) MENGGUNAKAN MODEL GUIDED INQUIRY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP SISWA - Asmawati, Eka Yuli (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The learning process in 2013 curriculum for all levels of education carried out by using a scientific approach (scientific approach). Critical thinking skills and mastery of concepts students need to developed in a learning process that is as capital to criticize a variety of symptoms, problems that arise in the vicinity. The use of instructional media and learning models in physics very aid learners in understanding the concepts of physics. Based on the above, it is necessary to do a literature review on the develop of guided inquiry worksheets with models to improve critical thinking skills and mastery of concepts students. The study began with highlights ofÂ LKSÂ and model of guided inquiry. Next, review the empirical research has done about critical thinking. Then the third part discusses the concept mastery. Furthermore, in the fourth part is the end of the literature review. Based on the literature study, the authors conclude that the developÂ the model of guided inquiry worksheets can used to improve critical thinking skills and mastery of concepts students.